2012
DOI: 10.1111/j.1755-3768.2012.02397.x
|View full text |Cite
|
Sign up to set email alerts
|

Extended mutation spectrum of Usher syndrome in Finland

Abstract: ABSTRACT.Purpose: The Finnish distribution of clinical Usher syndrome (USH) types is 40% USH3, 34% USH1 and 12% USH2. All patients with USH3 carry the founder mutation in clarin 1 (CLRN1), whereas we recently reported three novel myosin VIIA (MYO7A) mutations in two unrelated patients with USH1. This study was carried out to further investigate the USH mutation spectrum in Finnish patients. Methods: We analysed samples from nine unrelated USH patients ⁄ families without known mutations and two USH3 families wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…Visual symptoms manifest as retinitis pigmentosa (RP), a progressive retinal dystrophy, with rod and secondary cone photoreceptor dysfunction and ultimate loss. USH is a clinically and genetically heterogeneous disorder, making diagnosis and treatment challenging [ 6 9 ]. Previous studies categorized the morphological retinal findings of USH patients, showing that cystoid macula edema and/or cystic macular lesions (CML) are the most common complications in RP associated with USH (USH-RP) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Visual symptoms manifest as retinitis pigmentosa (RP), a progressive retinal dystrophy, with rod and secondary cone photoreceptor dysfunction and ultimate loss. USH is a clinically and genetically heterogeneous disorder, making diagnosis and treatment challenging [ 6 9 ]. Previous studies categorized the morphological retinal findings of USH patients, showing that cystoid macula edema and/or cystic macular lesions (CML) are the most common complications in RP associated with USH (USH-RP) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also illustrated this possibility [20,25,[29][30][31][32]. A study based in Italy found that one patient received the USH2A variant from the unaffected father and the MYO7A variant from the unaffected mother, which was heterozygous for mutations in both USH genes [20].…”
Section: Discussionmentioning
confidence: 99%
“…The gene was found to be connected to the USH3A subtype [ 93 , 94 , 95 , 96 , 97 , 98 ]. A founder mutation, p.Y176X, is present in Finland [ 99 ], but linkages to the USH3 region have also been found in families from the USA and Sweden. Founder mutation among Ashkenazi has been reported as being c.144T > C; p.N48K [ 97 ].…”
Section: Genetics Of Ushmentioning
confidence: 99%